2016
DOI: 10.1016/j.exer.2016.10.013
|View full text |Cite
|
Sign up to set email alerts
|

The Alzheimer's-related amyloid beta peptide is internalised by R28 neuroretinal cells and disrupts the microtubule associated protein 2 (MAP-2)

Abstract: Age-related Macular Degeneration (AMD) is a common, irreversible blinding condition that leads to the loss of central vision. AMD has a complex aetiology with both genetic as well as environmental risks factors, and share many similarities with Alzheimer's disease. Recent findings have contributed significantly to unravelling its genetic architecture that is yet to be matched by molecular insights. Studies are made more challenging by observations that aged and AMD retinas accumulate the highly pathogenic Alzh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 77 publications
0
14
1
Order By: Relevance
“…Of note, the disorganization of the outer retina in the model group was more severe in our study compared to other similar studies. 10,15,[35][36][37][38][39][40][41][42] Studies using Long-Evans rats 10 instead of C57BL/6 mice showed no morphologic changes or retinal cell apoptosis on retinal neurons in contrast to ours. Interestingly, in studies using Sprague-Dawley rats, 36,38 there were no morphologic changes, but retinal cell apoptosis appeared as early as day 2.…”
Section: Discussioncontrasting
confidence: 52%
“…Of note, the disorganization of the outer retina in the model group was more severe in our study compared to other similar studies. 10,15,[35][36][37][38][39][40][41][42] Studies using Long-Evans rats 10 instead of C57BL/6 mice showed no morphologic changes or retinal cell apoptosis on retinal neurons in contrast to ours. Interestingly, in studies using Sprague-Dawley rats, 36,38 there were no morphologic changes, but retinal cell apoptosis appeared as early as day 2.…”
Section: Discussioncontrasting
confidence: 52%
“…AMD is the most common cause of irreversible blindness in developed countries and especially in people over 60 years of age [ 80 ]. Early AMD is characterized by RPE dysfunction with the formation of drusen deposits between the RPE and Bruch’s membrane, generally in the macula, the central region of the retina [ 81 , 82 , 83 ]. Advanced AMD presents with progressive RPE degeneration and can develop into the exudative AMD (eAMD) with choroidal neovascularization (CNV) or non-exudative AMD (neAMD) with geographic atrophy (GA) [ 8 , 84 ].…”
Section: Age-related Macular Degenerationmentioning
confidence: 99%
“…However there is a limitation of the RGCs impairment model in replacement of RGCs with R28 retinal precursor cells. But R28 cells are immortalized retinal precursor cells that could differentiate into both neuronal and glial cell properties [29]. In a murine oxygen-induced retinopathy model, intravitreal injection of MSC-derived EVs reduced the severity of retinal ischemia [18].…”
Section: Discussionmentioning
confidence: 99%